The First National Unemployment Survey: Unemployment and the Canadian Census of 1891 - Baskerville, Peter; Sager, Eric (Labour/Le Travailleur, 1989)
Abstract The 1891 census asked Canadians if they had been unemployed in the week preceding the taking of the census. On the basis of a preliminary analysis of responses from working class areas in British Columbia, we comment on the nature of this source, and on the possibility of using it to determine both the extent of unemployment and the characteristics of the unemployed. We demonstrate our conclusion that this source has significant utility by testing the hypothesis that unemployment was a structural problem in the industrial capitalist labour market and not simply a result of specific deficiencies in part of the labour force.